RECONCEPTUALIZATION OF INDONESIA LAW SUBSTANCES - Rijadi, Prasetijo; Priyati, Sri (Brawijaya Law Journal, 2017)
Law is designed to bring justice to the people and to establish good public order. The idea of rule of law construction encouraged fundamental changes to the rule of law itself in accordance with country's values and interests. This article focuses on what exactly the substance of law and examines how such substance is understood by society. Furthermore, it analyses the application of such substance of law within the society and government organization. It further intends to enable articulating and emphasizing the law and its actual application in "the wholeness" and "helix" Re-conceptualization of conductive-correlative law substances to the understanding and meaning of the law as a norm that has social moment is necessary. The urgency to reconsider the construction of law substances is encouraged by the real fact, which law has deceived into supporting the power abuse, corruption, collusion and nepotism. This research argues that law is not just a normative abstraction, but also in its form as the totality of empirical phenomena that exist in social entities. Law should be understood in the sense of a dynamic, not static, and not general from the juridical elements. In the reformation era, only conceptual understanding that has the relevance.